Optimal photovoltaic system sizing of a hybrid diesel/PV system - Belhamadia A.; Mansor M.B.; Younis M.A. (Engineering and Scientific Research Groups, 2023)
Cost estimating; Costs; Optimization; Photovoltaic cells; Solar energy; Wind power; Climate condition; Cost estimations; Cost-efficient; Diesel generators; Hybrid optimization; Photovoltaic systems; Renewable energies; Standalone systems; Cost benefit analysis